DINAMEKA HUKUM TALAK DI INDONESIA DAN MESIR - Qadariyah, Lailatul (Qanuni : Journal of Indonesian Islamic Family Law, 2024)
This study examines the dynamics of divorce and divorce laws in family law legislation in Indonesia and Egypt as part of legal reforms aimed at improving the status of women in the context of Islamic family law. Through a comparative normative study, this study analyzes the laws in force in both countries, where Indonesia regulates divorce through Law No. 1 of 1974 concerning Marriage and the Compilation of Islamic Law (KHI) by emphasizing court procedures and mediation, while Egypt has been reforming since 1915 through a series of laws (Law No. 25 of 1920, 1929, to Law No. 100 of 1985) that are more progressive in granting women the right to file for divorce on expanded grounds such as inability to support, infectious diseases, arbitrary treatment, and neglect. The results of the study show that although the two countries use different approaches—Indonesia focuses on multi-layered court procedures and mediation, while Egypt on expanding women's rights—both have similar goals in protecting the rights of women and children and prioritizing justice, family protection, and legal certainty through official registration.